Nuclear Weapons And Strategy : U.S. Nuclear Policy For The Twenty-First Century. - Cimbala, Stephen J. (Taylor & Francis Ltd., 2005)
Focuses on the evolution of nuclear weapons as components of US military strategy and arms control, by contrasting their roles in the early and later information ages.